Effect of Tamarind (Tamarindus indica) Solution at Different Concentrations on Lead Content of Smoked Catfish (Pangasius sp) - Doni Marsal; Riya Liuhartana Nasyiruddin; Sofian Sofian; Steven Suryoprabowo; Abdellatief A. Sulieman (CV Media Inti Teknologi, 2024)
This research aims to study the effect of soaking smoked catfish in tamarind solution at various concentrations on its heavy metal content. A completely randomized design with one treatment used in the study, and concentrations of tamarind solution with four treatment levels were applied namely: 0% (A0 or control), 5% (A1), 10% (A2) and 15% (A3), each treatment with three repetitions. The lead (Pb) analysis showed that the control smoked catfish (A0) contained 0.307µg/g of Pb, exceeding the safe limit set by the Indonesian National Standardization Agency (BSN). Soaking in tamarind solution significantly reduced the Pb content in A1, A2, and A3 [by 89.57% (0.032µg/g), 97.39% (0.008µg/g) and 91.85% (0.025µg/g), respectively]. The hedonic test showed that the aroma and taste were significantly different. In addition, Post hoc test results revealed that the aroma of A1, A2 and A3 was significantly different from the control (A0); the taste of A1, A2 and A3 was significantly different from the control (A0); A1 was significantly different from A3. Based on the results, it could be concluded that the best treatment was A2 (10%).